Effectiveness of the Lorodent Probiotic Lozenge in Reducing Plaque and Streptococcus mutans Levels in Orthodontic Patients: A Double-Blind Randomized Control Trial - Ebrahim, Fatima; Malek, Sarah; James, Kris; MacDonald, Kyle; Cadieux, Peter; Burton, Jeremy; Cioffi, Iacopo; Lévesque, Celine; Gong, Siew-Ging (Frontiers in Oral Health, 2022)
Orthodontic patients are at a significant risk for oral diseases due to increased plaque accumulation and oral bacterial dysbiosis. We aimed to determine the efficacy of the commercially available Lorodent Probiotic Complex at reducing plaque accumulation and Streptococcus mutans bacterial levels in adolescent orthodontic patients. Sixty adolescents undergoing fixed orthodontic treatment for a minimum of 6 months were recruited in a randomized, double-blind, parallel-group, placebo-controlled trial. They received either Lorodent probiotic lozenge (intervention, n = 30) or placebo lozenge (control, n = 30) orally every day for a 28-day administration period. Participants were assessed at four appointments (T1–T4) over a total of 56 days. Compliance and lozenge satisfaction were monitored. Saliva samples and supragingival plaques were collected for evaluation of S. mutans levels. Clinical assessment using a Plaque Index (PI) was used. Compliance with lozenge intake of all participants was over 90%. There was no significant change in the PI and composite PI scores in both placebo and probiotic groups at each time frame (all p > 0.05) or the relative S. mutans DNA levels in the saliva and plaque between the probiotic and placebo groups. The findings of high compliance and satisfaction with the probiotic lozenges combined with the study's rigorous design offer a baseline for subsequent testing of further potential probiotics (of varying formulations, concentrations), especially in adolescents.